2017
DOI: 10.1086/689301
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Manipulation of Its Host’s Physiological Reaction to Acute Stress: Experimental Results from a Natural Beetle-Nematode System

Abstract: All animals, whether vertebrate or invertebrate, must be capable of reacting to acute stressors, such as escaping from predators, and most do so with a suite of transient physiological changes that temporarily enhance survival. Some of these changes include mobilization of immune cells and increased cardiac output. A small but growing number of studies have begun to show that certain parasites appear capable of modifying such responses. We addressed this topic using a natural host and parasite system, that is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Prior work in our lab using this host–parasite system also indicated how this nematode can negatively affect the immune activation that takes place during an acute stress reaction [ 22 ]. In that study, acute stress (mechanical tumbling) led to an increase in circulating hemocyte abundance in healthy beetles, but in parasitized beetles the hemocyte proliferation following stress was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior work in our lab using this host–parasite system also indicated how this nematode can negatively affect the immune activation that takes place during an acute stress reaction [ 22 ]. In that study, acute stress (mechanical tumbling) led to an increase in circulating hemocyte abundance in healthy beetles, but in parasitized beetles the hemocyte proliferation following stress was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Lower cardiac output would lead to less hemolymph distribution during stress, and by extension, fewer hemocytes being distributed during the stress event. Also of note from this prior work was that there was an attempt made to examine the effects of the nematode on ‘stressed’ beetle heartrates, and surprisingly, no effect was found [ 22 ]. However, in retrospect this probably had to do with the timing of the measurements; heartrates were measured before and after 10 min of mechanical stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like humans, beetles were also sensitive to heat as a source of physical stress, and at 45°C the corresponding values of HR in two groups increased to ~71 versus 69 beats min −1 (Davis et al, ). It was revealed that the “parasitism” did not influence the HR of host beetles Odontotaenius disjunctus and the mean values were 61 versus 64 beats min −1 when nematodes were absent.…”
Section: Introductionmentioning
confidence: 99%